The Value Of Knowledge In The Malay Mind: A Cognitive Semantic Analysis - Salehuddin, Khazriyati (Penerbit Universiti Sains Malaysia (USM Press), 2018)
knowledge is a universal concept that permeates all nations and civilisations. Like any other concepts, knowledge is also manifested in the form of fgurative expressions. Previous studies have shown that the fgurative expressions used in a particular language are closely related to the culture in which that particular language is used; this phenomenon is consistent with the linguistic relativity theory. In addition, studies in cognitive semantics have shown that the construction of fgurative expressions occurs systematically in the minds of its users. Thus, this paper describes how knowledge is represented in the Malay mind and how the concept is valued by the Malay speech community using the cognitive semantic approach. Specifcally, this paper illustrates how knowledge is valued by the Malay speech community through expressions related to knowledge via the use of three Idealised Cognitive Models, namely conceptual metaphors, metonymies and kinaesthetic image schemas. Results highlight the manifestation of knowledge fguratively in a variety of ways and this illustrates the manner the concept is perceived by the Malay speech community, i.e., knowledge is something big and is a source of light; hence, knowledge has to be sought in a proactive manner and that seeking knowledge is a life-long process. The fndings of this study suggest that knowledge can be discussed using the more universal conceptual metaphor the mind is the body, with diﬀerent manifestations of the conceptual metaphor.